High Temperature Fracture Toughness of Mullite with Monoclinic Zirconia - Glymond,D; Vick,M; Giuliani,F; Vandeperre,LJM (Journal of the American Ceramic Society, 2017)
Reactive sintering of zircon and alumina and zirconia additions to mullite are well establishedmethods for improving the poor fracture toughness of mullite. While it is clear that transformationtoughening is responsible for the improved toughness by addition of partially stabilised zirconia, it isnot clear why adding unstabilised zirconia increases the toughness although microcracking and crackdeflection have been suggested. Therefore the fracture toughness of a mullite composite with 20vol% unstabilised zirconia and a monolithic mullite were investigated at ambient conditions and attemperatures up to 1225 oC. It was found that monoclinic zirconia increases the toughness atambient conditions from the monolithic mullite value of 1.9 MPa m1/2 to 3.9 MPa m1/2. Thetoughness of the composite with zirconia remains relatively constant from ambient to 600 °C butthen decreases rapidly. The mechanism for the toughness enhancement as well as the reason for itsvariation with temperature are explained using changes in residual stress state as deduced using thesphere in shell model from the measured thermal expansion behaviour.